2016
DOI: 10.1007/s10802-016-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the General Factor of Psychopathology ‘p Factor’ Through Childhood and Adolescence

Abstract: Recent studies have suggested that the structure of psychopathology may be usefully represented in terms of a general factor of psychopathology (p-factor) capturing variance common to a broad range of symptoms transcending diagnostic domains in addition to specific factors capturing variance common to smaller subsets of more closely related symptoms. Little is known about how the general co-morbidity captured by this p-factor develops and whether general co-morbidity increases or decreases over childhood and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
198
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(225 citation statements)
references
References 64 publications
27
198
0
Order By: Relevance
“…Findings demonstrated that a general psychopathology (P) factor can be modeled in this community adolescent sample, as well as either (a) two specific externalizing and internalizing factors or (b) three specific ADHD/CD/ODD, substance use, and internalizing factors, providing further support for a spectrum and latent trait model of psychopathology (e.g., Caspi et al, 2014; Lahey et al, 2012, 2015; Murray et al, 2016). This study contributed to the literature by extending previous bifactor models to include eating disorders and a wider range of substance use symptoms.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Findings demonstrated that a general psychopathology (P) factor can be modeled in this community adolescent sample, as well as either (a) two specific externalizing and internalizing factors or (b) three specific ADHD/CD/ODD, substance use, and internalizing factors, providing further support for a spectrum and latent trait model of psychopathology (e.g., Caspi et al, 2014; Lahey et al, 2012, 2015; Murray et al, 2016). This study contributed to the literature by extending previous bifactor models to include eating disorders and a wider range of substance use symptoms.…”
Section: Discussionmentioning
confidence: 66%
“…Remarkably, these studies demonstrated that a general psychopathology factor (or P factor, as coined by Caspi et al, 2014) can be reliably replicated across samples and psychopathology disorders/symptoms, as well as developmental periods. Indeed, Murray, Eisner, and Ribeaud (2016) recently demonstrated that the P factor remained stable from age 7 to 16 years. Finally, these recent studies have also provided initial insights into the nature of the shared variance across psychopathology.…”
mentioning
confidence: 99%
“…However, due to strong associations between the dimensions themselves, a general psychopathological factor, p, has been proposed to explain the co-occurrence of virtually all psychiatric symptoms and disorders [6,7]. Although this general factor has been supported in both adult [6,7] and child samples [8,9], a consistent interpretation of the p-factor has so far proven elusive [6][7][8][9][10][11]. The most popular interpretation posits that p reflects a shared aetiological factor, or set of factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular interpretation posits that p reflects a shared aetiological factor, or set of factors (e.g. genetic vulnerability, personality, environmental factors) that predispose individuals to any and all forms of psychopathology [11].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the general psychopathology factor showed a significant Single nucleotide polymorphism (SNP) heritability of 38% (Neumann et al, 2016). Most of the studies above used DSM oriented scales; however, the general psychopathology factor was also replicated in studies using problem scales/items in general population samples (Laceulle, Vollebergh, & Ormel, 2015;Murray, Eisner, & Ribeaud, 2016). These new advances in discovering the component of psychopathology structure gave us an opportunity to develop psychopathology screening tool for I.…”
Section: Introductionmentioning
confidence: 99%